Pengaruh Gaya Kepemimpinan Transformasional dan Kompensasi Terhadap Kinerja Karyawan pada KSP Kopdit Obor Mas Maumere - Yohana Desiree Sadipun; Imanuel Wellem; Paulus Juru (Jurnal Projemen UNIPA, 2023)
This research aimed to (1) determine the description of Employee Performance, Transformational Leadership Style, and Compensation; (2) analyze the effect of Leadership Style and Compensation on Employee Performance either partially or simultaneously. The population in this study were employees of Obor Mas Maumere Credit Union as many as 45 people. Due to the limited population, this research was carried out by census or saturated sampling. Data were collected through questionnaires and analyzed using descriptive methods and inferential statistics, namely multiple linear regression. Hypothesis testing was carried out through F tests and t-tests. The results of the descrptive analysis revealed that the variables of employee performance, transformational leadership style, and compensation were categorized as good. The results of the t-test statistic showed that the transformational leadership style variable had a positive and significant effect on employee performance partially while compensation had a positive and insignificant efect on employee performance. The results of the F test statistic indicated that simultaneously the variables of transformational leadership style and compensation had a significant effect on employee performance. The determination analysis showed that the two independent variables in this study were able to explain the fluctuation of employees’ performance at Obor Mas Maumere Credit Union by 42.2%.